2021
DOI: 10.1002/ange.202016575
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo Natural Products—Chemical Evolution of Natural Product Structure

Abstract: Pseudo‐natural products (PNPs) combine natural product (NP) fragments in novel arrangements not accessible by current biosynthesis pathways. As such they can be regarded as non‐biogenic fusions of NP‐derived fragments. They inherit key biological characteristics of the guiding natural product, such as chemical and physiological properties, yet define small molecule chemotypes with unprecedented or unexpected bioactivity. We iterate the design principles underpinning PNP scaffolds and highlight their syntheses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…These limitations can be overcome by the design and synthesis of "pseudo-natural products" (pseudo-NPs). [3] In the pseudo-NP concept, NP fragments that represent NP structure and properties [4] are combined through de novo combination to afford unprecedented NP-inspired compound classes not accessible by known biosynthesis pathways. Pseudo-NPs inherit characteristic NP structures and properties but go beyond the chemical space explored by nature and, therefore, promise to have unexpected bioactivity and targets.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations can be overcome by the design and synthesis of "pseudo-natural products" (pseudo-NPs). [3] In the pseudo-NP concept, NP fragments that represent NP structure and properties [4] are combined through de novo combination to afford unprecedented NP-inspired compound classes not accessible by known biosynthesis pathways. Pseudo-NPs inherit characteristic NP structures and properties but go beyond the chemical space explored by nature and, therefore, promise to have unexpected bioactivity and targets.…”
Section: Introductionmentioning
confidence: 99%
“…Successfully, a nitrogen‐5‐membered ring fused to the 1,4‐benzoquinone system, compound II (indolequinone, Figure 1), exhibited good potency against tropical parasite Trypanosoma cruzi (IC 50 =20.0 nM and SI=625) [13] . Recently, a valuable strategy to identify new useful scaffolds, is the use of natural product‐derived fragments [15,16] . In this context, it was found that 2‐phenylbenzofuran scaffold is constituent of the structure of several bioactive natural products and has been used as a synthetic key intermediate for the construction of several biologically important compounds [17] .…”
Section: Introductionmentioning
confidence: 99%
“…This relevance calls for new approaches in order to discover compound classes that can be considered NP-inspired, but occupy unexplored areas of natural product-like chemical space. The recently introduced pseudo-natural product (PNP) approach [2] combines natural product fragments de novo and through different arrangements to yield compound classes that structurally resemble NPs but are not found in nature. [3] As a result, pseudo-NPs inherit typical properties of NPs from their respective NP fragments, [4] yet occupy biologically relevant chemical space not covered by existing NPs.…”
Section: Introductionmentioning
confidence: 99%